Addison's disease and its associations. (26th July 2013) - Puttanna, Amar; Cunningham, Alana Rosaleen; Dainty, Philip
Abstract : Addison's disease is a relatively rare endocrine condition resulting from adrenal insufficiency due to various causes. Weight loss is a common feature; however, patients may be seen by a variety of specialists, even requiring acute admission before the diagnosis is made. Addison's disease is commonly associated with other autoimmune diseases. In some cases such as autoimmune polyendocrine syndromes (APS) types 1 and 2, these associations are more commonly found. We present a case of one such patient who presented to the acute medical team having been referred to the gastrointestinal services in the previous year for persistent vomiting and weight loss. On review of history, the cause of vomiting and weight loss was questioned and combined with subsequent biochemical testing a diagnosis of Addison's disease was made. The patient was also noted to have other associated endocrine and autoimmune conditions.